2001
DOI: 10.1089/108729101753287685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adherence to Antiretroviral Therapy in HIV-1–Infected Patients at a University Public Service in Brazil

Abstract: The objective of this study was to assess if a simple evaluation, adherence to antiretroviral therapy, would correlate to clinical and laboratory outcomes. We followed an open cohort of patients from a public teaching hospital AIDS outpatient clinic. Patients were categorized according to adherence as: regular (Reg), optimal, all doses all days, tolerating only irregular timing (+/- 2 hours) of intake; quasi-regular (qReg), those missing up to four doses or 1 full day during a month; irregular (Irreg), all oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 7 publications
0
49
1
4
Order By: Relevance
“…"Regular" adherence was reported by 41% patients, "quasi-regular adherence" was reported by 19%, and "irregular" adherence was reported by the remaining 29%. Irregular adherence was independently associated with forgetfulness, intolerance, alcohol consumption, and misunderstanding of prescriptions 27 .…”
Section: The Challenges Posed By Non-adherence To Haartmentioning
confidence: 98%
See 1 more Smart Citation
“…"Regular" adherence was reported by 41% patients, "quasi-regular adherence" was reported by 19%, and "irregular" adherence was reported by the remaining 29%. Irregular adherence was independently associated with forgetfulness, intolerance, alcohol consumption, and misunderstanding of prescriptions 27 .…”
Section: The Challenges Posed By Non-adherence To Haartmentioning
confidence: 98%
“…25 . Such discrepancies in terms of what is being measured and how it is being measured may explain the variation observed, with a range of 52 to 83% of patients considered "adherent" to ARV therapy 26,27,28,29,30,31,32,33,34,35,36,37 .…”
Section: The Challenges Posed By Non-adherence To Haartmentioning
confidence: 99%
“…Alcohol consumption is the most prevalent risk factor for poor adherence to Highly Active Antiretroviral Therapy (HAART) among HIV-positive (HIV+) individuals, with approximately half of all persons reporting recent use (Golin et al, 2002;Chesney et al, 2000) While the cross-sectional association is well established (Paterson et al 2000, d'Arminio et al 2005Howard et al 2002;Brigido et al 2001;Haubrich et al 1999), recently it has been shown that there is a tightly coupled temporal association, with nonadherence on drinking days greatly exceeding nonadherence on nondrinking days in a particular patient sample (Braithwaite et al 2005a). This observation decreases the likelihood that the relationship between alcohol consumption and antiretroviral nonadherence is spurious and merely attributable to confounding.…”
Section: Introductionmentioning
confidence: 99%
“…This cohort has been followed up in the Ambulatory of the Secondary Immunodeficiency Clinic, Department of Dermatology of the Hospital das Clínicas, School of Medicine of the São Paulo University. More details regarding this cohort have been published elsewhere (Fonseca et al 1999, Brigido et al 2001). The statistical analysis was done using a nonparametric test (Mann-Whitney's test) to compare the groups, and the results presented in mean and standard deviation values, obtained with samples collected at the last available point (year 2000).…”
Section: Short Communicationmentioning
confidence: 99%